Anticariogenic Activity of Black Tea - An Invivo Study - Arya, Vishal (J Clin Diagn Res, 2016)
INTRODUCTION: Teas is known for its anticariogenic properties and various mechanisms have been invoked to explain this effect. One such proposed mechanism is inhibition of salivary alpha amylase activity by endogenous tannins present in tea. AIM: The objective of the present study was to determine whether or not the ingestion of black tea decoction inhibits the enzyme salivary amylase and thus interferes with the release of maltose from intraoral entrapped particles of food. MATERIALS AND METHODS: A total of 30 children in the age group of 12 - 15 years were selected for the study. After two hours of fasting subjects consumed two salted crackers for 60 second following which they rinsed with water (control solution) and then with 1.5% black tea decoction (test solution) next day. Retained food particles were recovered from buccal aspect of left mandibular premolar and salivary amylase activity was noted via chromatography. Paired t-test was applied for statistical analysis. RESULTS: Maltose to Sucrose ratio was used to evaluate the result. The average ratio was 3.27 for control solution and 1.82 for test solution. The results were statistically highly significant (p <0.005). CONCLUSION: Tea inhibited the activity of salivary amylase and this inhibition assumes a special significance when it is considered that the effect of tea could be manifested over a prolonged period of time, as in a real life situation.